2013
DOI: 10.1158/1541-7786.mcr-12-0496
|View full text |Cite
|
Sign up to set email alerts
|

mda-7/IL-24 Expression Inhibits Breast Cancer through Upregulation of Growth Arrest-Specific Gene 3 (gas3) and Disruption of β1 Integrin Function

Abstract: Melanoma differentiation-associated gene (MDA)-7)/interleukin (IL)-24, a member of the IL-10 family of cytokines, inhibits growth of various human cancer cells, yet the underlying mechanism is largely unknown. Here, we report that mda-7/IL-24 efficiently suppresses the development of rat mammary tumors in vivo. Microarray analysis for genes differentially expressed in rat mammary tumor cells overexpressing MDA-7/IL-24 compared with those that do not express this cytokine identified growth arrest-specific gene-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…PMP22/gas3 overexpression was originally found to induce an apoptotic-like phenotype, 91 and recent studies have revealed that the induction of GAS3 inhibits breast cancer by inhibiting the attachment and proliferation of the tumor cells, at least in part by blocking the interaction of β1 integrin with fibronectin. 92 Indeed, the tumor-suppressive activity of GAS3 is related to the significantly increased metastasis-free survival of breast cancer patients. Another top molecule notably decreased upon acquisition of metformin resistance was the S100A14 (S100 calcium binding protein A14) gene (14-fold downregulation vs. metformin-naïve MCF-7 cells; Table 2).…”
Section: P Value Ratiomentioning
confidence: 99%
“…PMP22/gas3 overexpression was originally found to induce an apoptotic-like phenotype, 91 and recent studies have revealed that the induction of GAS3 inhibits breast cancer by inhibiting the attachment and proliferation of the tumor cells, at least in part by blocking the interaction of β1 integrin with fibronectin. 92 Indeed, the tumor-suppressive activity of GAS3 is related to the significantly increased metastasis-free survival of breast cancer patients. Another top molecule notably decreased upon acquisition of metformin resistance was the S100A14 (S100 calcium binding protein A14) gene (14-fold downregulation vs. metformin-naïve MCF-7 cells; Table 2).…”
Section: P Value Ratiomentioning
confidence: 99%
“…PMP22 is expressed primarily in neural crest derived cell lineages (including melanocytes), however expression of PMP22 has also been associated with cell proliferation and survival in breast cancer [35]. To date no target genes of miR-4731 have been functionally validated.…”
Section: Introductionmentioning
confidence: 99%
“…IRF1 has similar expression profiles to IL24. Both IL24 and IRF1 are TSGs and exert anti-cancer activities via activation of STAT1 and STAT3 transcription factors [75,76,77,78]. Up-regulation of IL24 and IRF1 has anti-proliferative effects in breast and colon cancers [75,76,77,78].…”
Section: Vascular Endothelial Growth Factor (Vegf) Interleukin 8 (Ilmentioning
confidence: 99%